Penanggulangaan Kemiskinan di Kabupaten Luwu Utara menggunakan Pendekaatan Deep Interview - Maulida, Nur Aulyah; Bado, Basri; Irwandi, Irwandi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to determine the process and success of poverty alleviation carried out by the North Luwu district government. The data used in this study are cross-section data. The method of determining respondents is by using purposive random sampling which is snowball sampling. The research method used is a case study method with a qualitative approach. Data collection methods are observation and direct interviews. The data analysis technique uses QDA (Qualitative Data Analysis) which is divided into 4 important processes, namely, data collection, data reduction, data presentation and drawing conclusions (verification). The results of the study show that the main cause of poverty in North Luwu district is due to lack of income to meet basic needs such as food, housing, education and health, to meet these needs will always be related to spending. The largest expenditure comes from non-food expenditures, namely in housing and household facilities or the highest of all components of non-food needs of a household. Therefore, the government provides "house renovation" assistance through the BSPS program to poor people who have uninhabitable houses. In addition, other assistance such as BPNT, PKH and PBI are also given in cash to people who are categorized as poor in North Luwu Regency.